Exploring the effect of teaching methods on development of agricultural skills for food security: Case study of colleges of education in North-East Region, Nigeria - Umar, M. Abba; Daniel, I. (Kashere Journal of Education, 2023)
The study investigated teaching methods employed by agriculture lecturers in federal and state-owned colleges of education and its effect on students’ skills development for food security. Descriptive survey design was employed on a target population of 4,996 students and 84 agriculture lecturers. The actual sample size was 393 students and 77 agriculture lecturers. Data was collected using Agricultural Teachers 'Interview Timetable and Students' Focus Group Conversation Guide. The study found that discussion approach provides ways for the teacher to learn from the students and promote the application of the educational objectives. It equally revealed that demonstration method was the most significant approach to agricultural teaching that develops skills for food security. The views of the students suggest that discussion and demonstration are the most effective approaches to developing food security skills, but the most widely used method was lecturing.